Do stretch durations affect muscle mechanical and neurophysiological properties? - Opplert, J.; Genty, J.-B.; Babault, N. (International Journal of Sports Medicine, 2016)
The aim of the study was to determine whether stretching durations influence acute changes of mechanical and neurophysiological properties of plantar flexor muscles. Plantar flexors of 10 active males were stretched in passive conditions on an isokinetic dynamometer. Different durations of static stretching were tested in 5 randomly ordered experimental trials (1, 2, 3, 4 and 10×30-s). Fascicle stiffness index, evoked contractile properties and spinal excitability (Hmax/Mmax) were examined before (PRE), immediately after (POST0) and 5 min after (POST5) stretching. No stretch duration effect was recorded for any variable. Moreover, whatever the stretching duration, stiffness index, peak twitch torque and rate of force development were significantly lower at POST0 and POST5 as compared to PRE (P<0.05). Electromechanical delay was longer at POST0 and POST5 as compared to PRE (P<0.05). Whatever the stretch duration, no significant changes of Hmax/Mmax ratio were recorded. In conclusion, 30 s of static stretching to maximum tolerated discomfort is sufficient enough to alter mechanical properties of plantar flexor muscles, but 10×30?s does not significantly affect these properties further. Stretching does not impair spinal excitability.